Diversification of Learning Models in Strengthening Students’ Employability Skills: A Systematic Literature Review (2015–2025) - Indah Nursanti; Yoto Yoto; Imam Alfianto (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Nahdlatul Wathan Mataram, 2026)
This study aims to examine the diversification of learning models that strengthen employability skills among students of Vocational High Schools (Sekolah Menengah Kejuruan; SMK) based on scientific publications published from 2015 to 2025. Vocational High School (SMK) graduates are expected to master technical competencies while also possessing 21st-century skills, such as communication, teamwork, problem-solving, creativity, digital literacy, and leadership, to adapt to the demands of the business and industrial sectors in the era of the Industrial Revolution 4.0. This study employed a Systematic Literature Review (SLR) approach, following the PRISMA Statement protocol, to select and analyze relevant articles published over the past decade. The results of the review indicate that six main learning models support the improvement of employability skills, namely Project-Based Learning (PBL), Problem-Based Learning (PBL), Work-Based Learning (WBL), Teaching Factory (TeFa), Blended Learning or Flipped Classroom, and Cooperative Learning. Each model provides a distinct contribution: PjBL and PBL strengthen critical thinking, problem solving, and collaboration skills; WBL and TeFa enhance adaptability, professional communication, and technological literacy; Blended Learning emphasizes digital literacy and learner autonomy; while Cooperative Learning reinforces interpersonal communication, teamwork, and leadership. This study concludes that no single learning model can comprehensively accommodate all aspects of employability skills. Therefore, the diversification and integration of various learning models during the 2015 to 2025 period becomes an essential strategy for building a vocational education ecosystem that is relevant and responsive to industry needs